STUDI KOMPARATIF HARGA, LIKUIDITAS, DAN RISIKO SAHAM SEBELUM DAN SESUDAH PERUSAHAAN MELAKUKAN STOCK SPLIT DAN REVERSE SPLIT DI BURSA EFEK INDONESIA TAHUN 2004-2009 - Mardiyati, Umi; Khasanah, Khusfatun (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2011)
This research aim to analysis influence of stock split and reverse split to price (measured by daily closing price), liquidity (measured by bid-ask spread) and risk of the stock (measured by standard deviation), seen from there are difference before and after announcement of stock split and reverse split. Period of research during 2004 until 2009 with determination of sample use method of purposive sampling. Amount of taken company as sample 28 emiten of stock split and 7 emiten of reverse split. Secondary data used to be obtained by documentation of ISMD and IDX Statistics Quarterly. Technical analysis used for different test is paired sample t-test if data have normal distribution, if distribution of data is not normal used wilcoxon signed ranks test. While to test distribution of data used Kolmogorov-Smirnov test. The result of research show that there are difference of price among period before and after announcement of stock split and reverse split (Ha1 and Ha2 proven). Same with that, spread have difference too among period before and after reverse split (Ha4 proven). While spread didn’t have difference among period before and after announcement of stock split (Ha3 unprovable). Risk of stocks didn’t have difference among period before and after stock split and reverse split (Ha5 and Ha6 unprovable). Key words : stock split, reverse split, stock price, bid-ask spread, standard deviation.